Associations between nursing home performance and hospital 30‐day readmissions for acute myocardial infarction, heart failure and pneumonia at the healthcare community level in the United States. (17th May 2017) - Pandolfi, Michelle M.; Wang, Yun; Spenard, Ann; Johnson, Florence; Bonner, Alice; Ho, Shih‐Yieh; Elwell, Timothy; Bakullari, Anila; Galusha, Deron; Leifheit‐Limson, Erica; Lichtman, Judith H.; Krumholz, Harlan M.
Abstract : Objectives: To evaluate community‐specific nursing home performance with community‐specific hospital 30‐day readmissions for Medicare patients discharged with acute myocardial infarction, heart failure or pneumonia. Design: Cross‐sectional study using 2009–2012 hospital risk‐standardised 30‐day readmission data for Medicare fee‐for‐service patients hospitalised for all three conditions and nursing home performance data from the Centers for Medicare & Medicaid Services Five‐Star Quality Rating System. Setting: Medicare‐certified nursing homes and acute care hospitals. Participants: 12, 542 nursing homes and 3, 039 hospitals treating 30 or more Medicare fee‐for‐service patients for all three conditions across 2, 032 hospital service areas in the United States. Measurements: Community‐specific hospital 30‐day risk‐standardised readmission rates. Community‐specific nursing home performance measures: health inspection, staffing, Registered Nurses and quality performance; and an aggregated performance score. Mixed‐effects models evaluated associations between nursing home performance and hospital 30‐day risk‐standardised readmission rates for all three conditions. Results: The relationship between community‐specific hospital risk‐standardised readmission rates and community‐specific overall nursing home performance was statistically significant for all three conditions. Increasing nursing home performance by one star resulted in decreases of 0.29% point (95% CI: 0.12–0.47), 0.78% point (95% CI: 0.60–0.95) and 0.46% point (95% CI: 0.33–0.59) of risk‐standardised readmission rates for AMI, HF and pneumonia, respectively. Among the specific measures, higher performance in nursing home overall staffing and Registered Nurse staffing measures was statistically significantly associated with lower hospital readmission rates for all three conditions. Notable geographic variation in the community‐specific nursing home performance was observed. Conclusion: Community‐specific nursing home performance is associated with community‐specific hospital 30‐day readmission rates for Medicare fee‐for‐service patients for acute myocardial infarction, heart failure or pneumonia. Implications for practice: Coordinated care between hospitals and nursing homes is essential to reduce readmissions. Nursing homes can improve performance and reduce readmissions by increasing registered nursing homes. Further, communities can work together to create cross‐continuum care teams comprised of hospitals, nursing homes, patients and their families, and other community‐based service providers to reduce unplanned readmissions.